RESACRALIZATION OF CHILD CUSTODY AFTER DIVORCE IN ISLAMIC FAMILY LAW: BETWEEN THE PRINCIPLE OF MAṢLAḤAH AND THE CO-PARENTING TREND - Mukhamad Suharto; Kukun Abdul Syakur Munawar; Filda Vitalia; Muhammad Sadiq Ilham (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2025)
This article examines the resacralization of child custody (ḥaḍānah) in Islamic family law post-divorce, employing the principle of maṣlaḥah and the emerging global trend of co-parenting as complementary frameworks for reconstructing parental relations beyond marital dissolution. Classical Islamic jurisprudence tends to determine custody based on rigid biological and procedural norms, whereas contemporary social contexts increasingly acknowledge a child’s psychosocial and spiritual need for the presence of both parents. This study aims to explore how maṣlaḥah can serve as a normative basis to reformulate custody law in a child-centered and context-responsive manner, and to assess the potential incorporation of co-parenting within the Islamic legal system in Indonesia. Using a qualitative normative approach and analyses of religious court decisions, the findings suggest that restoring the sacred dimension of post-divorce parenting promotes not only spiritual values, but also expands justice for children. This research contributes to the development of progressive Islamic family law that prioritizes child welfare within both religious and legal paradigms.